Ocean bottom seismic model in the Knipovich Ridge area - Czuba, Wojciech; Murai, Yoshio; Janik, Tomasz; Górszczyk, Andrzej; Michalski, Krzysztof (Polish Polar Research, 2025)
The structure of the oceanic crust generated by the ultraslow-spreading mid-ocean Knipovich Ridge still remains relatively uninvestigated compared to the other North Atlantic spreading ridges further south. The complexity of the Knipovich Ridge, with its oblique ultraslow-spreading and segmentation, makes this end-member of Spreading Ridge Systems an important and challenging ridge to investigate. The Ocean Bottom Seismometer (OBS) data along a refraction/reflection profile (ca. 280 km) crossing the Knipovich Ridge off the western Barents Sea was acquired during cruise of RV G.O. Sars on July 24 to August 6, 2019. The seismic energy was emitted by air-guns with total volume of 80 l. To receive and record the seismic waves at the seafloor, ocean bottom seismometers were deployed. Seismic energy from airgun shots were recorded up to 50 km from the OBSs. The profile provides information on the seismic structure of the oceanic crust in the Knipovich Ridge area. Seismic record sections were analyzed with 2D trial-and-error forward seismic modeling. The crust thickness is variable and the Moho boundary depth changes between 7 and 12 km with P-wave velocity below the interface 7.9–8.0 km/s. The Moho discontinuity attains its minimum depth not directly beneath the Knipovich Ridge, but roughly 30 km to the southeast.